The Moderating Effect of Tourism By-Products on the relationship between Tourism Core Products and Destination Image (Sarawak, Malaysia) - Zahari, Mohd Salehuddin Mohd; Hanafiah, Mohd Hafiz; Ahmad, Emaria; Zain, Nur Adilah Md (Geographica Pannonica, 2017)
This paper reports an empirical investigation on the moderating effects of the tourism by- products in building Sarawak destination image. Using causal research design through a quantitative method, self-reported and self-administered questionnaire, this study surveyed international tourists who had visited Sarawak and experienced the state core tourism products which include purchasing the local tourism by-products. Through the descriptive and inferential statistics, some useful insights about the issue investigated were significantly obtained. It’s interesting to note that besides experiencing the tourism core products, the Sarawak Tourism by-products are also catching the international tourist’s attention. The moderating effect of tourism by-products on the relationship between tourism core products (culture, adventure, and nature) and Sarawak destination image was empirically confirmed. In fact, in addition to the core culture, adventure and nature product, the local tourism by- products undeniably building and strengthening the image of Sarawak as a tourist destination. This promising indication is, therefore, should not be ignored by the state government, tourism authority, tour operators, the local government, hotels and other related local authorities.